P3.044 HIV Risk Behaviors, in Juvenile Delinquents and in Family Abandonment Situations. Guatemala, 2012. (13th July 2013) - Huamán, B; Alvarez, B; Loya-Montiel, I; Osuna-Ramírez, I; Pinzón, Z; Mansur, M; Ortega, S; Vega, R; Morales-Miranda, S
Abstract : Background: Juveniles who are exposed to a street life are at high risk for drug addiction, pregnancy, sexually transmitted infections (STI), among others due to their biological, psychological and social vulnerabilities. Methodology: A survey was conducted in Guatemala City; with the purpose to determine risk behaviours and HIV and syphilis prevalence among juvenile delinquents and in family abandonment situations. A stratified consecutive sampling method was used; a tablet was used to conduct a standardised face-to-face questionnaire, and both pre-consent from legal guardians as well as assent by the minor were required. HIV and Syphilis screenings were conducted. Proportions and confidence intervals (CI 95%) adjusted for the sampling type were calculated using STATA 11.1. Results: 528 participants ages 15 to 17, 72% male and 28% female were enrolled. 58% (ICR 50.1–64.9) began having sexual relations between 10 and 14 years old, 37% (ICR 29.7–44.1) used a condom at first sexual act; only 24% (ICR 18.2–29.6) and 12% (ICR 9.11–15.0) had access to free condoms and HIV tests in the past year. 81% (ICR 75.7–85.8) reported currently being sexually active, 79% (71.22–85.67) had a stable partner, 20% (13.71–28.14%) occasional partner, and 1% (0.14–1.54) commercial partner; 40% (ICR: 32.8–47.9) reported using a condom a last sexual act. Out of the women surveyed, 16% (9.75–25.19) had been pregnant at one point and 53% of these had had an abortion. 57% (50–67.7) had consumed illicit drugs; marijuana making up 93% (ICR 87.8–96.6) and cocaine made up 31% (ICR 23.7–40.1) topping the list. HIV and Syphilis prevalences were lower than 1%. Conclusions: High pregnancy and illicit drug use proportions were reported, as well as low HIV and syphilis prevalences. Strengthening HIV prevention interventions, with an integral focus on reproductive sexual health adapted to this life stage and street context of this population, is necessary.